A computer-aided semi-quantitative seismic risk assessment tool for safe school buildings - Oreta, Andres Winston C. (Animo Repository, 2013)
Risk assessment is the first step in making schools safer against seismic hazards like ground shaking, liquefaction, tsunami and landslide. It is important that such risk assessments involve the primary stakeholders such as school administrators and officials, but the tools utilized by the agency responsible for such assessments, the Department of Public Works and Highways (DPWH) are limited to screeners with a good background of engineering. Employing a semi-quantitative risk assessment that assesses qualitatively the school building's assets, seismic hazards and vulnerabilities to the various hazards would allow the school administration and staff to participate in the decision-making process. A seismic risk index, defined as the product of these three factors categorizes the school buildings to be at low risk, medium risk or high risk to a specific seismic hazard. Through the computed indices, the school buildings in a specific compound are ranked and prioritized for further detailed inspections and possible repair or retrofitting. Mitigation procedures are recommended based on the identified vulnerabilities to reduce the risk. This paper presents the conceptual framework of the research and the semi-quantitative risk assessment methodology.